(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teaching a language and addressing the need of the learners is a complex and challenging exercise. Language plays a prominent role in teaching learning process; however, when it comes to teaching of English language, these challenges multiply especially, within the classroom context because of the learners and their diversity of choices. The Irony behind teaching and learning of English language lies in its context in the global level. English Language seems to have many challenges because of the need to proficiency, competency and fluency of users who are capable of utilising the language skills mainly, LSRW (Listening, Speaking, Reading and Writing) to gain employment in global markets. But today, teaching the learners the skills of the language has become more challenging because the learners exhibit a negative feeling to language classes. The present paper emphasises on making teachers more adaptable for the teaching process by avoiding various classroom discrepancies and preparing the learners to utilize new methods for better and effective skill-based language learning.